Machines and music: instrumental contributions to bluegrass. Issue 3 (December 2021) - Newton, Neil
Abstract: In the performance of bluegrass fiddle tunes, each repetition of the tune is generally played on a different instrument. I argue that the degree to which the instrument can influence the motivic material in improvised passages is beyond idiomaticism – where phrases might suit one instrument more than another – to the point where melodic pitch collections are shaped by the instrument itself. By combining post-human philosophies with music theories that emphasise instrument–player relationships, this essay shows how non-humans exercise agency in bluegrass improvisation. The resultant instrument-influenced passages contrast with each other, as each is played on a different instrument. This can help to signify formal structure within a performance, while the recurrence of particular instrument-influenced elements can be seen as a genre marker in bluegrass.